Can a Classroom Be a Family? Race, Space, and the Labour of Care in Urban Teaching - Gallagher, Kathleen (Canadian Journal of Education/Revue canadienne de l’éducation, 2016)
This article reports on findings from a case study of an eighth-grade teacher in an innercity school in downtown Toronto, Canada. It investigates the teacher’s pedagogical use of the metaphor of “family,” using interview data to underscore the effects produced by such an operating logic in a classroom. Methodologically, the article puts forward a novel analytic strategy to keep in dynamic interplay the relationship between how a teacher conceptualizes her teaching practice and where she locates those ideas. By focusing in-depth on one teacher’s pedagogical relations in the classroom, the article aims to better understand how teachers position the ubiquitous notion of “care” in their practice and how they enact “community” in their classrooms and in the larger schools and neighbourhoods in which they work. In this case study, the concepts and experiences of race and space are considered centrally in the examination of a racialized teacher’s pedagogical practices in a diverse and socio-economically marginalized school. The study has important implications for teacher education, inviting us to more explicitly acknowledge the salience of race in our conceptions of “care” and the investment of time and emotion that is demanded when practising politically conscious caring in teaching.